2012
DOI: 10.1161/hypertensionaha.111.178962
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Blood Pressure, Plasma β-Amyloid, and the Risk for Alzheimer Disease

Abstract: Beta-amyloid (Aβ), a vasoactive protein, and elevated blood pressure (BP) levels are associated with Alzheimer’s disease (AD) and possibly vascular dementia (VaD). We investigated the joint association of mid-life BP and Aβ peptide levels with the risk for late-life AD and VaD. Subjects were 667 Japanese-American men (including 73 with a brain autopsy), from the prospective Honolulu Heart Program/Honolulu Asia Aging Study (1965 – 2000). Mid-life BP was measured starting in 1971 participants mean age 58 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 40 publications
8
131
1
2
Order By: Relevance
“…In addition, prior evidence has suggested that arterial stiffness, blood pressure, and vascular disease strongly influence amyloid deposition in the brain and clinical manifestations of Alzheimer disease. [37][38][39] We also noted effect modification by age in our cohort, whereby larger effect sizes of the associations between abnormal arterial hemodynamics and neurocognitive dysfunction were seen in older individuals.…”
Section: Methods Study Participants the Framingham Heartsupporting
confidence: 67%
“…In addition, prior evidence has suggested that arterial stiffness, blood pressure, and vascular disease strongly influence amyloid deposition in the brain and clinical manifestations of Alzheimer disease. [37][38][39] We also noted effect modification by age in our cohort, whereby larger effect sizes of the associations between abnormal arterial hemodynamics and neurocognitive dysfunction were seen in older individuals.…”
Section: Methods Study Participants the Framingham Heartsupporting
confidence: 67%
“…The authors observed that A -related risk for AD positively correlated with blood pressure, suggesting that chronic hypertension may compromise vascular integrity and is a major contributor to CAA as well as impaired A clearance. 85 In support of these observations, animal studies using the spontaneously hypertensive stroke-prone rats, an animal model of chronic arterial hypertension and cerebral small-vessel disease, have demonstrated an age-dependent parenchymal A accumulation similar to that observed in AD models. 86 Additional studies in the spontaneously hypertensive stroke-prone rats rat reveal an age-specific increase in A deposition at 12 weeks of life, followed by APP overexpression at 20 weeks and p-tau by 26 weeks in the cortex and hippocampus.…”
Section: Hypertensionmentioning
confidence: 69%
“…14 In prior HAAS analyses, lower plasma b-amyloid was associated with an increased risk of Alzheimer disease and cerebral amyloid angiopathy at autopsy, particularly among those with elevated midlife blood pressure, suggesting that hypertension may lead to microvascular injury, promoting amyloid angiopathy and impaired b-amyloid clearance from the brain. 32 It has also been suggested that, among the elderly, aortic stiffness may increase pulsatile energy in the cerebral vasculature, with subsequent microvascular damage and thereby worsening of cognitive function. 33 We hypothesize that, among individuals with hypertension, BB use may provide neuroprotection through alterations in cerebral blood perfusion, improvement of microvascular integrity, and possibly reduction of subsequent neuropathology, including cerebral angiopathy, amyloid deposition, widening of periarteriolar spaces, microinfarcts, and atrophy.…”
Section: Resultsmentioning
confidence: 99%